A comparative study of cardiovascular disease risk factors among urban and rural population South Indian city - Junapudi, Syam Sundar; Babu Rao, B. (International Journal Of Community Medicine And Public Health, 2017)
Background: Non-communicable diseases are major health burden in the industrialized countries, and are increasing rapidly in developing countries like India due to demographic transition and changing lifestyles among people. Major Non communicable diseases are cardiovascular diseases, renal, nervous and mental diseases, musculoskeletal conditions, chronic non-specific respiratory diseases, permanent results of accidents senility, blindness, cancers, diabetes, obesity and various other metabolic and degenerative diseases and chronic results of communicable diseases. The aims and objectives of the study were to estimate the prevalence of cardio vascular disease risk factors among the study population above 15 years age group and to compare the study results between urban and rural area population. Methods: A total of 1400 persons in the age group of above 15 years were interviewed at their residence and anthropometric measurements were taken. The study design was on community based cross-sectional study. The study setting was on urban health centre, Harazpenta and rural health centre, Patancheruvu. The study population was on adults above 15 years of age in Harazpenta and Patancheruvu. The sample size was 700 urban, 700 rural population. The study period was on April 2008 to May 2009 (1 year). The data collection was by using pre-designed, pretested questionnaire. The data analysis was by using MS office 2003, Epiinfo 2007. The statistical test was on rates, ratios, proportions and Chi-square tests. Results: Smoking habit was more (19.2%) among urban population when compare to the rural (13.4%) population, alcohol use was 24%, when compared to 30.7% was alcohol use in rural area. In urban area 13.7% of population led with sedentary life, where as in rural area 3.3% only. Among urban population prevalence of obesity was 12.7% compared to 5.4% in rural population, prevalence of hypertension in urban area 18.7% and rural area 20%, In urban area prevalence of diabetes was 14.4% and in rural area. Conclusions: Smoking habit was more (19.2%) among urban population when compare to the rural (13.4%) population, in urban area alcohol use was 24%, whereas in rural area 30.7%. In the study population 14.5% of urban males led a sedentary life style, when compared with 5.1% of males in the rural area. Among urban population prevalence of obesity was 12.7% compared to 5.4% in rural area.